Komunikasi Vertikal dan Horizontal dalam Upaya Membentuk Gaya Kepemimpinan yang Demokratis Sesuai Prinsip Islam di Fakultas Adab UIN Raden Intan Lampung - Muhamad Bisri Mustofa; Siti Wuryan; Septiya Aristina; Sharah Nadine Vandira (Ath Thariq Jurnal Dakwah dan Komunikasi, 2021)
The success of an institution or company is closely related to a leader who is able to control a two-way communication. The world of IT was made the Raden Intan Lampung State Islamic University to launch two-way communication to make it easier to realize the goals or vision and mission of a university. It is undeniable that such communication has advantages and disadvantages, for example it often happens miscommunication caused by the loss of concern between employees or staff, superiors and subordinates at the University, then formality in a formal context has begun to disappear. The research that we conducted concerns vertical and horizontal communication at the Faculty of Adab, UIN Raden Intan Lampung, which which can be used as a reference for shaping democratic leadership it is hoped that it will add value to the quality of the university.